Economic feasibility of abscisic acid application to uniform ‘Rubi’ grapes coloration - Neto, Francisco José Domingues [UNESP]; Nachiluk, Katia; Fagundes, Priscilla Rocha Silva; Tecchio, Marco Antonio [UNESP] (Southern Cross Publishing, 2021)
São Miguel Arcanjo municipality (23º 31 ’S, 47º 35’ O and average altitude of 660 m) is part of one of the three main grape productive regions of São Paulo state, Brazil. The ‘Rubi’ grapes (Vitis vinifera) production constraint in that region is to achieve the variety characteristic coloration, which affects commercialization. The color of the berry grapes is due to the existence of anthocyanins and their accumulation seems to be at least in part regulated by abscisic acid. Therefore, exogenous applications of this regulator may increase the anthocyanins concentration in the grapes' skin. The aim of this paper is to evaluate the economic feasibility of abscisic acid application for treatment of the ‘Rubi’ grapes color uniformization and the impact of this application in the production cost. Production costs were calculated for the abscisic acid treated grapes and the non-treated grapes for a ‘Rubi’ grapes variety in the sixth year of production and recommended abscisic acid concentration for the region (400 mg L-1 at the beginning of the maturation + 200 mg L-1 at 25 days after first application). The abscisic acid was applied on the berry bunches in the morning using a backpack sprayer that provided full and uniform coverage. Economic feasibility was determined by the increment in the sale price of the final product due to the berries’ quality achieved with the treatment. The cost components measured were: production cost, variable and fixed cost quota, effective operational cost, total operational cost, operational profit and profitability index. Technical coefficients input prices, machinery and implements compose the production cost and were surveyed at the property where the experiment was performed. The cost structure is the Total Operating Cost to which social charges, machinery depreciation, interest rate and depreciation of a one-hectare area with a lifespan of 20 years were added. Prices paid to producers in the same period were collected from CEAGESP database for the profitability analysis. The Total Operating Cost for grape’s production with abscisic acid treatment was 26.12 % superior to the one of the grapes produced without the treatment, thus adding a US$ 0.15 increment in the paid price per kilogram of the final product. Therefore, this experiment has shown that abscisic acid application is a profitable investment that adds value to the final product cultivated in low thermal amplitude regions where the grapes cannot achieve the variety’s characteristic coloration.
Keywords: abscisic acid; anthocyanins; cost-effectiveness; Total Operating Cost; Vitis vinifera